131 Pharmacokinetics and Clinical Efficacy of Phenobarbital in Asphyxiated Newborns Treated with Therapeutic Hypothermia. (October 2012) - Broek, MPH van den; Groenendaal, F; Toet, MC; Straaten, HLM van; Hasselt, JGC van; Huitema, ADR; Vries, LS de; Egberts, ACG; Rademaker, CMA
Abstract : Background and aims: Therapeutic moderate hypothermia for neuroprotection in the asphyxiated newborn can influence pharmacokinetics and pharmacodynamics. If seizures occur, phenobarbital is the anticonvulsant of first choice. The aim of this study was to evaluate the effect of therapeutic hypothermia on phenobarbital pharmacokinetics and to evaluate the clinical efficacy of phenobarbital under hypothermia. Methods: Data were obtained from a prospective study in two Dutch level III NICUs (SHIVER-study). Term born newborns with criteria of perinatal asphyxia and encephalopathy were included. Therapeutic hypothermia (33.5 o C) was started within 6 hours after birth and was maintained for 72 hours. Pharmacokinetic modelling was performed using NONMEM. Results: In total, 31 term-born newborns were included of which 87 plasma samples were obtained (69 samples during the hypothermic phase). Based on a one-compartmental model with allometric relationships, clearance and distribution volume were estimated at 17.2 mL/h/3.5kg and 3450 mL/3.5kg respectively. No relationship between hypothermia and pharmacokinetic parameters was identified. Overall, 66% of all neonates demonstrated sufficient seizure control with phenobarbital monotherapy, even though 69% of all measured concentrations were below 20 mg/L. In 88% of neonates with recurrent seizures during phenobarbital therapy, plasma concentrations were predicted to be < 20 mg/L at the moment of recurrent seizures. This supports a minimal effective concentration of about 20 mg/L. Conclusion: Also during hypothermia we advise an initial 20 mg/kg loading dose. However, clinicians should not be reluctant to administer an additional dose of 10–20 mg/kg, as we have shown that the blood levels were often below the therapeutic range (20–40 mg/L).